Normalizing Online Gambling Through Multimodal Food and Beverage Advertising Imagery - Vivit Novita Axviarani; Reza Safitri; Fitri Hariana Oktaviani (FAKULTAS DAKWAH UIN SALATIGA, 2026)
Online gambling advertisements have become increasingly prevalent across Indonesian social media platforms, although gambling is legally prohibited in Indonesia. These advertisements employ covert advertising strategies by masquerading as online gambling through familiar food and beverage imagery. Multimodal elements are utilized as a persuasive strategy to shape and normalize gambling practices. This study critically examines how multimodal elements are constructed in covert advertisements format and how these constructions contribute to the normalization of online gambling practices within Indonesian digital culture. The study demonstrates how multimodal elements operate as persuasive strategies in covert online gambling advertisements. Drawing upon Multimodal Critical Discourse Analysis (MCDA), the study analyzes three advertisements collected from the Meta Ads Library in 2025 that masquerade as Mie Sedaap (instant noodles), Potabee (snacks), and Sprite (soft drinks). The findings reveal two dominant normalization discourses. First, gambling is normalized as a familiar and risk-free consumption practice through symbolic associations with familiar food and beverage imagery. This process reflects a form of symbolic domestication, in which gambling is gradually relocated from a stigmatized and illegal activity into an ordinary and culturally familiar consumption practice. Second, gambling is normalized as an enjoyable and rewarding activity through promotional language emphasizing guaranteed winning and high financial profits, ultimately fostering an instant success fantasy. These findings contribute to critical discussions on covert advertising and online gambling normalization in Indonesia.